2016
DOI: 10.4103/0973-1296.176047
|View full text |Cite
|
Sign up to set email alerts
|

Influence of chitosan nanoparticles as the absorption enhancers on salvianolic acid B In vitro and In vivo evaluation

Abstract: Background:Salvianolic acid B (SalB) represents the most abundant and bio-active phenolic constituent among the water-soluble compounds of Salvia miltiorrhiza. But the therapeutic potential of SalB has been significantly restricted by its poor absorption.Methods:In this study, chitosans (CS) and CS nanoparticles (NPs) with different molecular weights (MWs), which have influence on the absorption of SalB, was also investigated.Results:As a preliminary study, water-soluble CS with various MWs (3, 30, 50, and 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Previous pharmacokinetic study has provided a hint that DO volatile oils mostly distributed and accumulated on rat intestine might affect the absorption of other drug ingredients 34 , but it has not been elucidated experimentally. In the present study, with the presence of DO volatile oils in QSYQ, the absorption of major ingredients in QSYQ, such as CS, ON, CG, PCA, TSL, RA, SAB, AIV were obviously enhanced compared to the absence of DO volatile oils in QSYQ-DO in isolated intestinal tract, especially for ON, CG, RA, SAB and AIV 35 38 , which have larger molecular weights and possess poor permeability across the intestinal epithelium.…”
Section: Discussionmentioning
confidence: 49%
“…Previous pharmacokinetic study has provided a hint that DO volatile oils mostly distributed and accumulated on rat intestine might affect the absorption of other drug ingredients 34 , but it has not been elucidated experimentally. In the present study, with the presence of DO volatile oils in QSYQ, the absorption of major ingredients in QSYQ, such as CS, ON, CG, PCA, TSL, RA, SAB, AIV were obviously enhanced compared to the absence of DO volatile oils in QSYQ-DO in isolated intestinal tract, especially for ON, CG, RA, SAB and AIV 35 38 , which have larger molecular weights and possess poor permeability across the intestinal epithelium.…”
Section: Discussionmentioning
confidence: 49%
“…This was further corroborated by a recent study that concluded that the absorption-enhancing effect of chitosan was drug-dependent, with acyclovir displaying unfavorable enhancement of absorption in the presence of chitosan [84]. On the other hand, there are studies that highlighted drugs that displayed an enhanced absorption with the aid of chitosan, and these include molecules such as buserelin, [ 14 C] mannitol, and dextran [79,85].…”
Section: Chitosanmentioning
confidence: 55%
“…The permeation rate and P app value of salvianolic acid B were found to be at a maximum when co-delivered with chitosan displaying a molecular weight of 100 kDa. However, with a decreasing molecular weight, the researchers also observed a decline in the permeation rate of salvianolic acid B [79]. It was proposed that the chitosan, which exhibits a positive surface charge, forms ionic interactions with the negatively charged glycocalyx groups, resulting in the reversibility of the opening tight junctions, which could improve the paracellular drug transport.…”
Section: Chitosanmentioning
confidence: 99%
“…18 Indeed, these nano-sized carriers overcome intrinsic challenges encountered by drug molecules in gastrointestinal tract, and can also be modified to maintain the required drug release for therapeutic response. 19 Wide range of biocompatible polymers from synthetic and natural sources with specific properties have been explored for the formulation of nanoparticles intended for oral delivery. Among these, synthetic polymers are widely preferred as they possess good mechanical strength and can be modified to obtain well-defined release characteristics.…”
Section: Introductionmentioning
confidence: 99%